Europe's dependence on US foreign military sales and what to do about it - Juan Mejino-López; Guntram B. Wolff (Bruegel, 2025)
Worries about Europe's dependence on the United States military industrial base have increased with the worsening security situation in Europe and the deterioration of the transatlantic relationship. With a new dataset covering all notifications under the US Foreign Military Sales programme since 2008, we show that Europe has substantially increased its purchases from the US defence industrial base during the last four years, deepening its dependence on US military equipment in the short to medium term. The dependence is particularly significant for high-tech equipment, including air defence, missiles and fighter jets, and for additional equipment and services included in purchases, such as advanced software and sustainment and modernisation required in future years. This strategic reliance on the US, even when the risks associated are low, provide the US with significant bargaining leverage over Europe that can potentially be used in different policy areas, such as trade. Moreover, the US military industrial base faces its own constraints and current and future US administrations might prioritise deliveries to Asia. In response, European policymakers must assess the extent of dependence on the US and develop a strategy on how to minimise the risks. At a time of rising defence budgets, it is crucial that European production of key weapon systems grows faster than demand, so that dependence on the US defence industrial base is gradually reduced. Policymakers should review critical technological dependencies, even for procurement directed at national producers, and should plan to upgrade Europe's technological base without increasing external dependence. Learning from and cooperating with Ukraine to boost Ukrainian production is one important step. Establishing a timeline to determine the pace at which certain dependencies should be minimised is equally necessary. Europe also needs to reduce its reliance on structural strategic systems provided by the US, such as command, control and communications systems. Given the diverging strategic cultures across Europe, building consensus is of paramount importance. European companies need to grow to the scale that is only achievable in a larger market. Failing to implement a strategy risks Europe losing its freedom and autonomy.
Keywords: 330